The Effect of Secubitril and Valsartan Combination on Mortality in Patients with Heart Failure in Our Local Set Up - Ibrahim Shah, Akhtar Sher, Saif Ullah, Matiullah Khan, Samiullah Khan, Umer Ibrahim Paracha, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Heart failure (HF) is a major health problem and better patient outcomes need novel therapies. Objective: The purpose of this research was to evaluate impact of combination of sacubitril and valsartan on mortality in individuals with HF in our local setting. Methodology: Our research was a prospective cohort and included a total of 600 patients on valsartan and sacubitril and 600 control individuals. Data was collected for baseline demographic, clinical and outcome variables and examined. To compare death rates of the two groups, Kaplan-Meier survival analysis was used and hazard ratios were computed to evaluate variations in risk. A p-value of less than 0.05 indicates statistically significant differences. Results: At two years, the survival rate for the sacubitril and valsartan group was 92.17% (553 patients) compared to 87.67% (526 patients) in the control group. Mortality rates were lower in the sacubitril and valsartan group at 7.83% (47 patients) versus 12.33% (74 patients) in the control group. The outcome was a hazard ratio of 1.31 (95% CI: 0.95-1.80), which suggests that sacubitril plus valsartan combination significantly decreased mortality. Conclusion: Sacubitril plus valsartan combination dramatically increased survival rates in heart failure patients when compared to usual care, indicating that this medication has the potential to be a useful therapy for lowering mortality in this group of patients. Keywords: Heart Failure, Sacubitril, Valsartan, Mortality, Survival Analysis